Validation with the Dynamic Prediction Model of Protein and Amino Acid Requirements for Growth Performance and Health in Layer Chicks - Zhi-Yuan Xia; Alainaa Refaie; Miao Liu; You-Yang Wei; Lv-Hui Sun; Zhang-Chao Deng (Animals, 2025)
This study evaluated an established dynamic prediction model for protein and amino acid nutritional requirements on growth performance and health in layer chicks. A total of 288 one-day-old healthy Jing Tint 6 chicks were randomly divided into four treatment groups with 6 replicates of 12 chicks each. The chicks in the four groups were fed a basal diet (BD) according to the feeding standards and a model diet (MD) based on the dynamic prediction model for protein and amino acid values at 90%, 100%, or 110% for 6 weeks. The results showed that, compared to the BD, the 110% MD increased (p < 0.05) the FI and the 100% MD had no effect (p > 0.05) on FI, BWG, and FCR of chicks throughout the entire feeding phase. The 90% MD, however, significantly reduced (p < 0.05) FI and BWG, while also increasing (p < 0.05) FCR during the 3–6- and 0–6-week periods. Additionally, compared to the BD, the 100% MD had a lower (p < 0.05) intake of crude protein, methionine, lysine, and threonine than that of the BD. Both the 100% and 110% MDs increased (p < 0.05) bursa weight and its index at the 2nd week, while the 90% MD reduced (p < 0.05) the weights of the liver, spleen, and pancreas at the 6th week when compared to the BD. Moreover, the 100% MD increased (p < 0.05) the weights of the duodenum and jejunum, while the 90% MD decreased (p < 0.05) jejunum and ileum length at the 2nd or 6th week. Furthermore, no differences (p > 0.05) were found in serum ALT, AST, BUN, and UA between the 100% MD and BD groups. In conclusion, the dynamic prediction model can minimize protein waste while supporting healthy growth and development in layer chicks.